A systematic review of outcome reporting in laser treatments for dermatological diseases. (10th October 2019) - Fransen, F.; Tio, D.C.K.S.; Prinsen, C.A.C.; Haedersdal, M.; Hedelund, L.; Laubach, H.J.; Marini, L.; Paasch, U.; Passeron, T.; Wolkerstorfer, A.
Abstract: The standardization of outcome reporting is crucial for interpretation and comparison of studies related to laser treatment of skin disorders. In collaboration with the Cochrane Skin‐Core Outcome Set Initiative (CS‐COUSIN), a procedure has been proposed to find consensus on the most important generic outcome domains (what to measure) for implementation in the international Laser TrEAtment in Dermatology (LEAD) registry. As the first step in the development of a generic outcome set for the LEAD registry, we undertook a systematic review to identify outcomes, outcome measurement instruments, methods and definitions reported in recently published literature of laser treatments for skin disorders. A systematic search was conducted and generated a total of 707 papers. We assessed 150 studies including all types of studies involving laser treatments for the skin. Two researchers independently extracted the type, definition and frequency of all outcomes and used outcome measurement instruments. We identified 105 verbatim outcomes that were categorized into eight domains recommended by the COMET framework: appearance, long‐term effects, physician and patient‐reported physical signs, satisfaction, health‐related quality of life, psychological functioning and adverse events. Heterogeneity in outcome reporting (e.g. categories and outcome measurement instruments) was high, and definitions were insufficiently reported. There was a clear under representation of life impact domains, including satisfaction (23%) quality of life (3%) and psychological functioning (1%). Outcome reporting concerning laser treatments for the skin is heterogeneous. Standardized outcomes are needed for improving evidence synthesis. Results of this review will be used in the next step to reach consensus between stakeholders on the outcome domains to be implemented in the LEAD registry.